1997
DOI: 10.1021/jp962099v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding of Water to Phosphatidylcholine in the Membrane As Studied by a Molecular Dynamics Simulation:  Location, Geometry, and Lipid−Lipid Bridging via Hydrogen-Bonded Water

Abstract: Hydrogen (H-) bonding between water and phosphatidylcholine was studied using a molecular dynamics simulation of a hydrated phosphatidylcholine bilayer membrane in the liquid crystalline phase. A membrane in the liquid-crystalline phase composed of 72 l-α-dimyristoylphosphatidylcholine (DMPC) and 1622 water molecules was generated, starting from the crystal structure of DMPC. At the beginning of the equilibration process, the temperature of the system was raised to 550 K for 20 ps, which was effective in break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
227
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(256 citation statements)
references
References 68 publications
28
227
1
Order By: Relevance
“…Molecular dynamics simulations found that water molecules connect different phospholipids and that the lifetime of these water bridges is up to 50 ps. 47 Thus, the water shell around phosphate groups in phospholipids is comparably rigid and fluctuating molecular motions to a substantial extent suppressed. Moreover, due to the tilt of phospholipid head groups, this hydration shell water is partly shielded from the surrounding bulk, i.e., the electric force exerted by bulk water fluctuations on both interfacial water and PO − 2 oscillators is much weaker than the dipole forces originating from the head groups.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics simulations found that water molecules connect different phospholipids and that the lifetime of these water bridges is up to 50 ps. 47 Thus, the water shell around phosphate groups in phospholipids is comparably rigid and fluctuating molecular motions to a substantial extent suppressed. Moreover, due to the tilt of phospholipid head groups, this hydration shell water is partly shielded from the surrounding bulk, i.e., the electric force exerted by bulk water fluctuations on both interfacial water and PO − 2 oscillators is much weaker than the dipole forces originating from the head groups.…”
Section: Discussionmentioning
confidence: 99%
“…CHARMM-GUI 21,22 was employed to generate six sets of lipid bilayers with cholesterol concentrations [CHOL] varying between 0% and 50%. Each system consisted of 72 cholesterol / dimyristoylphosphatidylcholine (DMPC) 23,24 molecules, 3600 water molecules described by the modified TIP3P model 25,26 , and a pair of Na + and Cl − described by the CHARMM36 force field 27,28 . In contrast to other force fields (such as GROMOS), the CHARMM36 force field generates a less pronounced adsorption of Na + ions on phosphatidylcholine (PC) membranes, which was shown to be consistent with structural Xray measurements and experiments on chain ordering of PC lipid bilayers in the presence of NaCl 29 .…”
Section: System Setup and Equilibrationmentioning
confidence: 99%
“…Details concerning the construction of the POPC and PEPC molecules and subsequently bilayers, as well as the initial simulations of these bilayers, were described in Murzyn et al (36). Details concerning the DMPC bilayer were described in Pasenkiewicz-Gierula et al (44,45).…”
Section: Simulation Systemsmentioning
confidence: 99%